Resolved Tooth Discolouration Following Root Fracture Employing a Conservative Approach: A Case Report - Kheirabadi, Nasir; Parirokh, Masoud; Fereidooni, Rahim; Manochehrifard, Hamed (Iranian Endodontic Journal, 2019)
Dental trauma is one of the most common childhood incidents that leads to the damage or loss of deciduous and permanent teeth. One of the most challenging types of dental trauma is horizontal root fracture (HRF). In this case report, a central maxillary incisor with horizontal root fracture‎ had been treated by the conservative approach of splinting the tooth and follow-up. In the initial evaluation, the tooth had a normal appearance and did not respond to either the cold test or electric pulp tester. After 4 weeks, the tooth was sensitive to the cold test; however, showed discolouration. After 4 months, discolouration disappeared and the tooth had a positive response to pulp sensibility tests. The tooth remained asymptomatic with a positive response to pulp sensitivity tests up to 15 months following the treatment. Keywords:Discolouration, Horizontal Root Fracture; Pulp Vitality; Trauma